Improvement of Knowledge, Behavior and Health of Pregnant Women in Preventing Prenatal Stunting - Agustin Wulan Suci Dharmayanti; Amandia Dewi Permana Shita; Zahara Meilawaty; Oktavia Nur Vitasari (Health Notions, 2022)
Stunting is a growth failure due to malnutrition in the first thousand days of a child's life, affecting growth and development during adulthood. The prevalence of stunting in the Bondowoso Regency reached the national prevalence, about 38%. One of the causes is inadequate nutrition of the mother during pregnancy. Malnutrition in pregnant women induces anemia, especially iron deficiency. This condition affects infant growth and development. The public health center regularly gives pregnant women iron tablets to prevent it. However, not all pregnant women are aware of the advantage of good nutrition and iron tablets. This study aimed to examine changes in aspects of health, knowledge, and behavior in anemia pregnant women after specific nutrition interventions, education, and mentoring. This study was qualitative with a case study design, which used in-depth interviews and direct observation toward respondents and assistance to three anemia pregnant women in Cindogo Village, Bondowoso Regency. The data collected were primary and secondary about respondents’ health status, knowledge of nutrition, and behavior of living style. The data obtained were analyzed descriptively. The result showed that before education, the respondents were not aware of their nutrition. However, after intervention and mentoring, they know about the advantages of nutrition and iron tablets and are also aware of their health and infants. Briefly, the respondent’s awareness about prenatal stunting, nutrition, and health during pregnancy changed. This alteration was expected to be able to prevent prenatal stunting in Cindogo Village, Bondowoso Regency. Keywords: knowledge; behavior; health; pregnant women; prenatal stunting